Impact of corporate social responsibilities on employee perception of Mutual Trust Bank Limited - Riya, Zannatul Ferdous (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.